THE STUDENT’S ACCURACY IN USING DISCOURSE MARKERS FOR ACADEMIC WRITING (A CASE STUDY OF STUDENTS IN ENGLISH AND LITERATURE DEPARTMENT (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This research focused on the accuracy of discourse markers used by the students in their academic writing, especially in the thesis background. This research used a qualitative method, analyzed by Bruce Fraser (1999) to identify the elaborative markers. The result of data analysis in this research found the types of discourse markers used in students’ thesis background, which are: the first is contrastive markers such as whereas, otherwise, even though, in contrast, and yet. The second is elaborative markers such as besides, in other words, also, for example, furthermore, and. The last is inferential markers such as so, because, in this case, hence, therefore, then, and in this case. On that basis, the dominant type of discourse markers used in students’ thesis background was elaborative markers which were applied about 11 times. In addition, the researcher found there were 20 discourse markers that were used in the student’s thesis background. The result of this research showed that only 16 of the discourse markers were used in an appropriate way and 4 of them were used in an inappropriate way
Keywords: Discourse Markers; Academic Writing; Student’s Accuracy